1998
DOI: 10.1007/s002689900473
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Spontaneous Pneumothorax: Ten‐year Experience

Abstract: Spontaneous pneumothorax (SP) is commonly observed in young, tall, thin subjects without apparent underlying lung disease and in the elderly with chronic emphysematous lung disease. We present our experience in treating SP during the last decade. From December 1986 to November 1996 a total of 417 consecutive patients with SP were admitted to our department. There were 349 males (83.7%) and 68 females, ranging in age from 14 to 93 years. A right-side SP was detected in 234 cases (56.1%), a left-side SP in 175 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
2
26
0
2
Order By: Relevance
“…34 Several authors have quoted their own definition of a ''persistent air leak'' and the point at which they would consider progression to an invasive surgical procedure (Table 1). [3][4][5][6][7][8][9] Reviews of series of adult patients have suggested delaying surgical intervention for 5-10 days, in contrast to reviews of younger patients that have urged early intervention. These suggestions are, at best, expert-based, with little or no supporting evidence.…”
Section: Introductionmentioning
confidence: 99%
“…34 Several authors have quoted their own definition of a ''persistent air leak'' and the point at which they would consider progression to an invasive surgical procedure (Table 1). [3][4][5][6][7][8][9] Reviews of series of adult patients have suggested delaying surgical intervention for 5-10 days, in contrast to reviews of younger patients that have urged early intervention. These suggestions are, at best, expert-based, with little or no supporting evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Although standard posterolateral thoracotomy is still used to treat SP [90], recent reports show that there is a preference for smaller incisions: axillary thoracotomy [91,92], anterior thoracotomy [93], muscle-sparing lateral thoracotomy [94], and a variety of posterior, lateral and axillary mini-thoracotomy procedures [95]. Midsternotomy for simultaneous treatment of both lungs is performed in ,1% of cases [95].…”
Section: Surgical Management By Thoracotomymentioning
confidence: 99%
“…Common complications include persistent air leaks, usually defined as leaks persisting for .5 days, and occur in 5-7% of patients [94,95], wound infection (1.4-6.7%) [94], pneumonia (2.4-8%) [93,94], fever (1.9-10%) [94,95], re-operation due to bleeding (1-2%) [90,93] and shoulder arthritis (1.9%) [95]. Other complications, such as residual pneumothorax, urinary tract infection, acute urinary retention, haematoma or neurological deficit, are rare [90].…”
Section: Surgical Management By Thoracotomymentioning
confidence: 99%
“…SP cerrahi tedavisinde standart posterolateral torakotomi ile yaklaşım halen kullanılmasına rağ-men yayınlanan son raporlar daha küçük insizyonla (aksiler mini torakotomi, anterior torakotomi, lateral torakotomi) yapılan cerrahi yaklaşımlara karşı bir eğilim olduğunu göster-mektedir. [44][45][46] British Thoracic Society'nin son raporlarında spontan pnö-motoraks cerrahisinde VATS ve alternatif stratejilerde kontrollü klinik çalışma eksikliği nedeniyle en düşük nüks oranlarına sahip torakotomi ve plörektomi prosedürlerinin tercih edilmesi önerilmektedir. [47] Deslauriers ve ark.…”
Section: Discussionunclassified